Changes in Paraspinal Muscles and Facet Joints after Minimally Invasive Posterior Lumbar Interbody Fusion Using the Cortical Bone Trajectory Technique: A Prospective Study - Yue Li; Yuxiang Chen; Yuzeng Liu; Yong Hai; Xinuo Zhang; Li Guan; Tianqing Zhang (Pain Research and Management)
In this prospective cohort study, we aimed to determine the surgical and adjacent segment changes in paraspinal muscles and facet joints in patients with lumbar spinal stenosis after minimally invasive posterior lumbar interbody fusion (PLIF) using the cortical bone trajectory (CBT) technique. We enrolled 30 consecutive patients who underwent the single-level CBT technique between October 2017 and October 2018. We evaluated preoperative and 1-month, 3-month, 6-month, and 1-year postoperative clinical data including Visual Analogue Scale (VAS) scores and Oswestry Disability Index (ODI). Magnetic resonance imaging (MRI) was performed a year after surgery. The erector spinae (ES) muscle area, volume, and fat infiltration (FI) on the surgical and adjacent segments were evaluated using the thresholding method, and the degree of adjacent facet joint degeneration was calculated using the Weishaupt scale. FI rate was graded using the Kjaer method. All patients underwent a 12-month follow-up. The VAS and ODI scores significantly improved after surgery in all patients. No patient showed degeneration of the adjacent facet joints (P>0.05) during the 1-year follow-up postoperation. There was no significant difference in ES muscle volume, area, and FI on the surgical and adjacent segments (P>0.05). The FI rate of the upper ES muscles increased postoperatively (P<0.05); however, there were no significant changes in FI rate of the lower ES muscles. Patients with lumbar spinal stenosis could obtain satisfactory short-term clinical outcomes via minimally invasive PLIF using the CBT technique. Moreover, this technique may reduce the impact on the paravertebral muscles, especially the ES muscle, and the adjacent facet joints.